Comparative studies on control of thermal environment in development headings using force/exhaust overlap ventilation systems. (June 2021) - Xin, Song; Wang, Wenhao; Zhang, Ningning; Zhang, Cong; Yuan, Shuo; Li, Hao; Yang, Wenyu
Abstract: Auxiliary overlap ventilation systems have been widely used in development headings of underground mines, but their cooling performance has been rarely reported. To fill this gap and extend the work on the modeling and computational studies of mine ventilation and air conditioning, the cooling performances of the two arrangements of these systems, which are far-forcing-near-exhausting (FFNE) and near-forcing-far-exhausting (NFFE) configurations are studied through field measurements and numerical simulations. Comparisons of the air velocity, temperature, relative humidity distribution, and heat transfer between FFNE and NFFE ventilation systems confirmed the superior cooling performance of the latter. In addition, thermal comfort and ventilation efficiency evaluation indices are introduced to evaluate the ventilation and cooling performance for different exhaust-to-forcing volume flow rate ratios ( R e/f ) and air duct locations. The optimal R e/f values and air duct locations are obtained through numerical simulations. The results show that the ventilation system should be applied reasonably based on the main hazard at the heading face. NFFE ventilation system is more suitable for solving the heat generation challenge. In this study, in order to achieve the optimal ventilation and cooling performance, it is recommended to set R e/f to 1.5, install the outlet of the forcing air duct at 3 m away from the heading face, and the inlet of the exhausting air duct at 12 m away from the heading face during the mucking operation. This study will contribute to the design of auxiliary ventilation systems for optimizing ventilation and cooling systems in blind headings. Highlights: Ventilation and cooling performances of two kinds of auxiliary overlap ventilation systems are compared. Heat transfer criterion correlation of these two ventilation systems are developed. Recommended values for the configuration setting of the ventilation system are proposed.